Sedation Strategy, Procedural Comfort, and Clinically Detected Radial Artery Spasm During Transradial Coronary Angiography: A Prospective Observational Study - Uğur Karagöz; Senem Girgin; Mehmet Ali Coşar; Fahrettin Tuğrul Çitekçi; Tolunay Demirbaş; Ecem Büger; Büşra Tozduman; Sadık Volkan Emren; Murat Aksun (Journal of Clinical Medicine, 2026)
Background/Objectives: Radial artery spasm (RAS) is the most common periprocedural complication of transradial coronary angiography (TRA) and is identified clinically, from patient-reported forearm pain and operator-perceived catheter resistance, rather than by imaging. This study compared two sedation strategies used in routine clinical practice, namely fentanyl-midazolam moderate sedation (MS) and a propofol-integrated monitored anaesthesia care (MAC) regimen, with respect to procedure-related pain and the incidence of clinically detected radial artery spasm (cRAS). Methods: This single-centre, prospective, non-randomised, observational study enrolled 394 consecutive patients undergoing elective TRA (MS, n = 231; MAC, n = 163). cRAS was defined as at least two of five established criteria: three patient-reported pain items and two operator-perceived resistance items. No angiographic, ultrasonographic or physiological assessment of radial vasomotor tone was performed, and operators were not blinded. Co-primary endpoints were cRAS and post-procedural pain scores; the secondary endpoint was a composite of periprocedural complications. Factors associated with cRAS were analysed using multivariable logistic regression, including sensitivity analyses with decreasing dependence on patient-reported pain. Results: cRAS occurred in 59 patients (15%), 20.3% with MS and 7.4% with MAC (p = 0.001). VAS pain scores were lower with MAC (p < 0.001); complications did not differ (13.4% vs. 7.3%; p = 0.083). Female sex (odds ratio [OR] 3.60; 95% confidence interval [CI] 1.91–6.78), procedural duration (OR 1.04 per minute; CI 1.02–1.06) and MS rather than MAC (OR 3.69; CI 1.80–7.58) were independently associated with cRAS (all p < 0.001). The association persisted when the outcome was restricted to operator-assessed criteria (21.6% vs. 9.2%; OR 2.95; CI 1.55–5.59). Conclusions: The propofol-integrated regimen was associated with less procedural pain and less clinically detected spasm. These hypothesis-generating findings describe clinically apparent spasm and cannot establish prevention of true vasospasm. Within that limit, they support testing this strategy in a randomised trial with objective, blinded endpoints, particularly in women.